Assessment of immunological anti‐platelet factor 4 antibodies for vaccine‐induced thrombotic thrombocytopenia (VITT) in a large Australian cohort: A multicenter study comprising 1284 patients. (29th September 2022) - Favaloro, Emmanuel J.; Clifford, Joanne; Leitinger, Emma; Parker, Michael; Sung, Pauline; Chunilal, Sanjeev; Tran, Huyen; Kershaw, Geoffrey; Fu, Suki; Passam, Freda; Ahuja, Monica; Ho, Shir Jing; et al.
Abstract: Background: Vaccine‐induced thrombotic thrombocytopenia (VITT) is a rare complication of adenovirus‐based vaccines aimed to prevent and minimize COVID‐19 and related pathophysiology. Objectives: To describe patterns of testing for anti‐platelet factor 4 (PF4) antibodies using various ELISA assays in a large Australian cohort and comparative functional platelet activation assays in a subset. Patients/Methods: Asserachrom HPIA IgG ELISA was performed in 1284 patients over a period of 12 months, supplemented in select cohorts by comparative ELISA using three other methods ( n  = 78–179), three different functional assays (flow cytometry, serotonin release assay, and/or Multiplate; n  = 476), and rapid immunological chemiluminescence anti‐PF4 assay ( n  = 460), in a multicenter study. Results: For first episode presentations, 190/1284 (14.8%) ELISA tests were positive. Conversely, most (445/460; 96.7%) chemiluminescence anti‐PF4 test results were negative. All functional assays showed associations of higher median ELISA optical density with functional positivity and with high rates of ELISA positivity (64.0% to 85.2%). Data also identified functional positivity in 14.8%–36.0% of ELISA negative samples, suggesting false negative VITT by HPIA IgG ELISA in upward of one third of assessable cases. Conclusion: To our knowledge, this is the largest multicenter evaluation of anti‐PF4 testing for investigation of VITT. Discrepancies in test results (ELISA vs. ELISA or ELISA vs. functional assay) in some patients highlighted limitations in relying on single methods (ELISA and functional) for PF4 antibody detection in VITT, and also highlights the variability in phenotypic test presentation and pathomechanism of VITT.